2009
DOI: 10.1211/jpp/61.05.0016
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin inhibits melanin synthesis in melanocyte cells

Abstract: This study suggests that the depigmenting effect of silymarin might be attributable to inhibition of tyrosinase expression and that silymarin may be useful as a natural skin-lightening agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Silymarin can also reduce melanin production by its antioxidant effect and inhibition of L‐dopa oxidation activity of tyrosinase. In addition, it has been found that silymarin decreases the expression of tyrosinase protein …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Silymarin can also reduce melanin production by its antioxidant effect and inhibition of L‐dopa oxidation activity of tyrosinase. In addition, it has been found that silymarin decreases the expression of tyrosinase protein …”
Section: Discussionmentioning
confidence: 99%
“…Complete dermatological examination was also performed to assess Fitzpatrick skin type, pattern of melasma (centro-facial, malar, or mandibular), melasma type (epidermal, dermal, or mixed) and severity as assessed by melasma area and severity index score (MASI Score). 4 The severity of melasma was divided according to MASI score into mild (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), moderate (>16-32), and severe (>32-48).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silybum marianum L.) Downregulated tyrosinase protein in mouse melanocyte cell line (Choo et al, 2009). …”
Section: Silymarin (Milk Thistle Ormentioning
confidence: 99%